2022
DOI: 10.1021/acsomega.2c00661
|View full text |Cite
|
Sign up to set email alerts
|

tREPs─A New Class of Functional tRNA-Encoded Peptides

Abstract: We asked if transfer RNA (tRNA) ever got an opportunity of translating its own sequence during evolution, what would have been the function of such tR NA-encoded p eptides (tREPs)? If not, could one artificially synthesize tREPs to study the corresponding functional outcomes? Here, we report a novel, first-in-the-class, chemically synthesized tREP-18 molecule originating from the Escherichia coli tRNA sequence showing potent antileishmanial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Subsequently, dark genome sequences were artificially expressed in E.coli, D.melanogaster and S.cerevisiae leading to antimalarial, antimicrobial and anti-cancer molecules (Joshi et al, 2013, Raj et al, 2015, Deepthi et al, 2017. Recently, tRNA sequences were used to produce tREPs (tRNA encoded peptides) showing a strong anti-leishmania properties (Chakrabarti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, dark genome sequences were artificially expressed in E.coli, D.melanogaster and S.cerevisiae leading to antimalarial, antimicrobial and anti-cancer molecules (Joshi et al, 2013, Raj et al, 2015, Deepthi et al, 2017. Recently, tRNA sequences were used to produce tREPs (tRNA encoded peptides) showing a strong anti-leishmania properties (Chakrabarti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae leading to antimalarial, antimicrobial and anti-cancer molecules (Joshi et al, 2013, Raj et al, 2015, Deepthi et al, 2017). Recently, tRNA sequences were used to produce tREPs (tRNA encoded peptides) showing a strong anti-leishmania properties (Chakrabarti et al, 2022). in this study, sequences of known protein-coding genes in E .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, tRNA sequences of E. coli were expressed into tREPs showing strong antileishmania properties (Chakrabarti et al, 2022). Recently it was observed that antisense Sequences (Garg & Dhar, 2023) and reverse Sequences (Nayak & Dhar, 2023) can be artificially encoded into stable and functional protein molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no dataset of monofunctional RNA available. In particular, it is challenging to annotate RNAs as ‘strictly non-coding’, as even tRNAs have recently been shown to encode peptides ( 16 ). This limits the present study to the computation of the TPR and the false negative rate (FNR), calculated as:…”
Section: Methods Performancementioning
confidence: 99%
“…To a lesser extent, other classes of ncRNAs may also be translated ( 15 ), such as circular RNAs (circRNAs), transcripts from untranslated regions (UTR), primary microRNAs (pri-miRNAs), ribosomal RNAs (rRNAs), and some archaeal and bacterial small RNAs (sRNAs). Most recently, transfer RNAs (tRNAs) have also been shown to be translated into functional peptides ( 16 ). In terms of application, these transcripts are notably of medical and agronomic interests, as they have been shown to be tightly associated with cancer ( 17 ) and to play various regulatory roles in plants ( 18 ).…”
Section: Introductionmentioning
confidence: 99%